The relationship between screen-based sedentary behaviors and symptoms of depression and anxiety in youth: a systematic review of moderating variables - Jennifer Zink; Britni R. Belcher; Kellie Imm; Adam M. Leventhal (BMC, 2020)
Abstract Background To elucidate the populations and conditions where screen-based sedentary behaviors (SB) and internalizing symptoms are coupled, this review synthesized the evidence for factors that may moderate the associations between screen-based SB, depressive symptoms, and anxiety symptoms among youth. Methods Two independent researchers conducted a systematic literature search of the Medline, psycINFO, and Scopus electronic databases in late 2018 for observational studies assessing moderators of the association between screen-based SB and depressive and anxiety symptoms. Studies among children and adolescents were eligible if moderation was assessed by statistical test (interaction) or stratification; and a narrative synthesis of eligible studies was conducted in accordance with PRISMA guidelines. Results Seventy empirical studies (46 cross-sectional, 19 longitudinal, and 5 both) of 13 different moderating variables of screen-based SB-internalizing symptom associations met the eligibility criteria. Of these, 40 studies were of depressive symptoms, 2 were of anxiety symptoms, and 28 studies assessed symptoms of both. The most consistent evidence of moderation was for screen-type, such that TV viewing was not as strongly associated with internalizing symptoms compared to other forms of screen-based SB. There was also inconsistent evidence for physical activity buffering screen-based SB-internalizing symptom associations and for female sex amplifying screen-based SB-internalizing symptom associations. In general, the body of evidence for anxiety symptoms was more limited than that for depressive symptoms, and were therefore more inconsistent. Conclusions Screen-type, physical activity, and sex may influence the magnitude of screen-based SB-internalizing symptom coupling; highlighting potential sources of heterogeneity of screen-based SB-internalizing symptom associations. Additional studies aimed at understanding potential mechanistic explanations for the above moderators are needed prior to the development of tailored intervention strategies designed to decouple screen-based SB and internalizing symptoms among youth.